2023
DOI: 10.1111/head.14617
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic cluster headache with burst and tonic occipital nerve stimulation: A case series

Ida Stisen Fogh‐Andersen,
Jens Christian Hedemann Sørensen,
Rigmor Højland Jensen
et al.

Abstract: Objectives and BackgroundChronic cluster headache (CCH) is a rare but severely debilitating primary headache condition. A growing amount of evidence suggests that occipital nerve stimulation (ONS) can offer effective treatment in patients with severe CCH for whom conventional medical therapy does not have a sufficient effect. The paresthesia evoked by conventional (tonic) stimulation can be bothersome and may thus limit therapy. Burst ONS produces paresthesia‐free stimulation, but the amount of evidence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Based on our previous experience with ONS treatment [ 26 ], we estimate that 50% of the participants who receive active treatment with burst ONS will reach the primary endpoint of a 30% reduction in attack frequency. A blinded trial with burst ONS and placebo has to our knowledge not been carried out earlier, but we hypothesize that no more than 10% in the placebo group will meet the primary endpoint [ 35 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous experience with ONS treatment [ 26 ], we estimate that 50% of the participants who receive active treatment with burst ONS will reach the primary endpoint of a 30% reduction in attack frequency. A blinded trial with burst ONS and placebo has to our knowledge not been carried out earlier, but we hypothesize that no more than 10% in the placebo group will meet the primary endpoint [ 35 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…A novel stimulation paradigm termed burst stimulation, originally designed for spinal cord stimulation for chronic neuropathic pain, has given rise to paresthesia-free stimulation [ 24 ]. The scientific evidence on burst stimulation used for ONS is scarce, but in two small studies, it has been suggested that paresthesia-free burst stimulation may have a similar effect as tonic ONS reducing attack frequency in CCH patients [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%